CROSS-SECTORAL ECONOMIC LAW IN INDONESIA: A LITERATURE REVIEW OF THE INTERACTION BETWEEN DEVELOPMENTAL ECONOMIC LAW AND SOCIAL ECONOMIC LAW IN THE DYNAMICS OF BANKING, INDUSTRY, AGRICULTURE, AND NATIONAL TRADE - Shohib Muslim; Hadenan Towpek (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2026)
This study examines the interaction between development economics law and social economics law within the framework of cross-sectoral economic law in Indonesia, focusing on the dynamics of the banking, industrial, agricultural, and national trade sectors. Through a legal-normative approach and qualitative analysis of various literature, regulations, and economic policies, this study shows that the two legal regimes are not dichotomous, but rather complement and correct each other in an effort to achieve sustainable and equitable development. The results of the study emphasise the need for an integrative economic law paradigm that explicitly accommodates the synergy between economic growth, equitable distribution of development outcomes, protection of vulnerable groups, and environmental sustainability in every cross-sectoral policy.